Respuesta :

C B A are the orders of the answers

Answer:

1.  [tex]y=(x+3)^2-4[/tex]

2. [tex]y=(x+4)^2-3[/tex]

3. [tex]y=(x-3)^2+4[/tex]

4. [tex]y=(x-4)^2+3[/tex]

Step-by-step explanation:

The vertex from of a quadratic function is

[tex]y=a(x-h)^2+k[/tex]

where, a is constant and (h,k) is vertex.

(1)

The vertex of the parabola is (-3,-4).

[tex]y=a(x-(-3))^2+(-4)[/tex]

[tex]y=a(x+3)^2-4[/tex]

The graph is passes through the point (-1,0).

[tex]0=a(-1+3)^2-4[/tex]

[tex]4=4a[/tex]

[tex]1=a[/tex]

[tex]y=(1)(x+3)^2-4[/tex]

[tex]y=(x+3)^2-4[/tex]

Therefore, the required equation is [tex]y=(x+3)^2-4[/tex].

Similarly,

(2)

The vertex of the parabola is (-4,-3).

[tex]y=a(x+4)^2-3[/tex]

The graph is passes through the point (-3,-2).

[tex]-2=a(-3+4)^2-3[/tex]

[tex]a=1[/tex]

Therefore, the required equation is [tex]y=(x+4)^2-3[/tex].

(3)

The vertex of the parabola is (3,4).

[tex]y=a(x-3)^2+4[/tex]

The graph is passes through the point (2,5).

[tex]5=a(2-3)^2+4[/tex]

[tex]a=1[/tex]

Therefore, the required equation is [tex]y=(x-3)^2+4[/tex].

(4)

The vertex of the parabola is (4,3).

[tex]y=a(x-4)^2+3[/tex]

The graph is passes through the point (3,4).

[tex]4=a(3-4)^2+3[/tex]

[tex]a=1[/tex]

Therefore, the required equation is [tex]y=(x-4)^2+3[/tex].